Post-Operative Complications and Nipple Necrosis Rates Between Conventional and Robotic Nipple-Sparing Mastectomy - Lee, Jeea; Park, Hyung Seok; Lee, Haemin; Lee, Dong Won; Song, Seung Yong; Lew, Dae Hyun; Kim, Jee Ye; Park, Seho; Kim, Seung Il (Frontiers in Oncology, 2021)
Purpose This study is the first to directly compare surgical outcomes between conventional nipple-sparing mastectomy (CNSM) and robot-assisted nipple-sparing mastectomy (RNSM). Materials and method For this case-control study, 369 cases of 333 patients who underwent CNSM or RNSM with immediate reconstruction between November 2016 and January 2019 at Severance Hospital in Seoul, Republic of Korea were reviewed. Patients with stage IV breast cancer (n=1), receiving neoadjuvant chemotherapy (n=43), or subjected to previous operations (n=14) or radiotherapy on the breasts were excluded. The main outcomes were comparing rates of post-operative complications, of high-grade post-operative complications as defined by the Clavien-Dindo classification, and nipple necrosis between the CNSM and the RNSM groups. Results A total of 311 cases, including 270 CNSMs and 41 RNSMs, were analyzed. The rates of post-operative nipple necrosis (p = 0.026, 2.4% vs. 15.2%) and of high-grade post-operative complications (p = 0.031, 34.8% vs. 17.1%) in the RNSM group were significantly lower than those in the CNSM group. Conclusion RNSM was associated with lower rates of high-grade post-operative complications and nipple necrosis than CNSM for patients with small breast volumes and less ptotic breasts.